2005
DOI: 10.1093/sleep/28.12.1543
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Atrial Fibrillation and Central Sleep Apnea

Abstract: We conclude that there is a markedly increased prevalence of atrial fibrillation among patients with idiopathic central sleep apnea in the absence of congestive heart failure. Moreover, the high prevalence of atrial fibrillation among patients with idiopathic central sleep apnea is not explainable by the presence of hypertension or nocturnal oxygen desaturation, since both of these were more strongly associated with obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 29 publications
3
46
0
3
Order By: Relevance
“…Our findings were also consistent with previously published work which shows an association between SDB and conditions such as diabetes [17] and atrial fibrillation [18,19].…”
Section: Cardiovascular Morbiditysupporting
confidence: 94%
“…Our findings were also consistent with previously published work which shows an association between SDB and conditions such as diabetes [17] and atrial fibrillation [18,19].…”
Section: Cardiovascular Morbiditysupporting
confidence: 94%
“…OSA has mainly been associated with premature atrial complex short runs, sinus bradycardia, sinus pauses, premature ventricular complexes and paroxysmal atrial fibrillation [9][10][11], while central sleep apnoea (CSA) has mainly been associated with atrial fibrillation [12]. There is also evidence for a close temporal relationship between arrhythmia and obstructive apnoeas [13].…”
mentioning
confidence: 99%
“…The effect of hypoxia on atrial fibrillation, however, was not significant. Although these results were based on self-reported heart failure, the authors suggested that their results agree with those of Leung et al (2005), that atrial fibrillation is more strongly associated with CSA than OSA, even in the absence of heart failure. They concluded that it may be beneficial to screen patients with AF for CSA.…”
Section: Atrial Fibrillationmentioning
confidence: 60%
“…Requiring an AHI of at least 15 as diagnostic for OSA, a case control study failed to show a difference in OSA prevalence between 59 patients with lone atrial fibrillation (i.e., without chronic or acute risk factors) and controls who were age, gender, and co-morbidity matched controls (32% vs. 29%; P=0.67) (Porthan et al, 2004). Another study (Leung et al, 2005) that excluded patients with a history of congestive heart failure (CHF), CAD, or stroke, enrolled 60 patients each without SBD, with CSA, and with OSA. The prevalence of atrial fibrillation was significantly higher in patients with CSA (27%) compared with OSA (1.7%) or no SBD (3.3%; P<.001).…”
Section: Cardiac Arrhythmias In Community-based Studies and In Subjecmentioning
confidence: 99%